Drivers and Trends of Irregular Migration: The Push and Pull Factors Responsible for the Japa Syndrome in Nigeria - Nwokolobia, Anthony C.; Ikenga, Francis A.; Sanubi, Franklins A. (LOGIKA : Jurnal Penelitian Universitas Kuningan, 2024)
Migration has changed over time in reaction to happenings and events around the world. The present surge in irregular migration was spurred by the absence of equitable social, political, and economic possibilities in many nations across the world. People are encouraged to go for better possibilities in other regions due to the unequal chances. This study therefore addressed the causes and trends of irregular migration in Nigeria with an emphasis on the push and pull variables that contribute to Nigerians' Japa syndrome. The collected data was analysed using the trend analysis approach, and the study employed a historical research design. This study concluded that migration is a means of pursuing greater possibilities abroad due to a chronic lack of work opportunities, income prospects, profitable employment, safety, and security, among other things. Fundamentally, economic opportunism that is, the enhancement of one's standard of living, the welfare of one's family, and other aspects that may guarantee the significance and relevance of the individual and their household contextualizes irregular migration in Nigeria. Since 2019, there has been a noticeable increase in the rate of migration abroad. Many young, bright, active, and industrious youths have been pushed to leave the country by these conditions, and this has resulted in the "Japa Syndrome or Japa Wave" in Nigeria.